Defining "System": a Comprehensive Approach. Issue 1 (July 2017) - Sillitto, Hillary; Dori, Dov; Griego, Regina M.; Jackson, Scott; Krob, Daniel; Godfrey, Patrick; Arnold, Eileen; Martin, James; McKinney, Dorothy
Abstract: Over the past decades, a common definition of the term system has eluded researchers and practitioners alike. We reviewed over 100 current and historical definitions of system in an effort to understand perspectives and to propose the most comprehensive definition of this term. There is much common ground in different families of definition of system, but there are also important and significant differences. Some stem from different belief systems and worldviews, while others are due to a pragmatic desire to establish a clear definition for system within a particular community, disregarding wider considerations. In either case, it limits the effectiveness of various system communities' efforts to communicate, collaborate, and learn from the experience of other communities. We discovered that by considering a wide typology of systems, Bertalanffy's General Systems Theory provides a basis for a general, self‐consistent sensible framework, capable of accommodating and showing the relationships amongst the variety of different definitions of and belief systems pertaining to system . Emergence, the appearance of a new phenomenon or capability as a result of relation or interaction between objects, is key in differentiating between objects that are systems and those that are not. Hence we propose a family of definitions, related by the common theme of emergence, which is in line with both the realist and constructivist worldviews, and covers real and conceptual systems. We believe this better reflects the current scope of systems engineering and is required to support the aspirations expressed in INCOSE SE Vision 2025.